Cryogenic Deformation Structures in Late Cenozoic Unconsolidated Sediments of the Tunka Depression in the Baikal Rift Zone. (30th April 2014) - Alexeev, Sergey; Alexeeva, Ludmila; Kononov, Alexander
ABSTRACT The Late Cenozoic alluvial deposits in the Tunka depression of the Baikal Rift Zone, Russia, contain wedge‐shaped structures and involutions that provide valuable palaeogeographic information about the southern part of eastern Siberia. The structure of the unconsolidated host deposits, the shape and size of the deformation structures (wedge shaped, wave like or drop like) and the physical‐mechanical properties of the sediments (particle size, density, porosity, water content and colour) point to a cryogenic origin of the deformation structures, as ice wedge pseudomorphs and cryoturbations, rather than an origin associated with seismic activity or sedimentation. The oldest pseudomorphs and cryoturbations developed during climate‐warming periods of the subboreal climatic phase (3600–2600 years ago). Copyright © 2014 John Wiley & Sons, Ltd.